What does subject-integrated teaching on key global issues in the social studies subjects in Swedish upper primary school look like, and what does it imply for teachers and students? - Tord Göran Olovsson (University of Aberdeen, School of Education, 2021)
This study aims to describe and analyse two cases in Swedish upper primary school, of subjectintegrated theme works in social studies subjects, specifically on key global issues. This research was conducted in the context of subject-integrated teaching in social studies subjects being currently quite rare, and that social studies subjects are sometimes neglected in early school years. However, based on previous research, subject-integrated teaching in these subjects may promote students' learning on key societal and global issues. Working with two student groups in two schools, this study was based on classroom observations, interviews with teachers and students, and students' written reflections. In the study, it is concluded that in subject-integrated theme work, it is important to permit the subjects to integrate in a rewarding way, with careful and well-thought-out teacher planning. However, there is also a need for openness and flexibility in ongoing teaching, especially when it may be conducive for students' learning to link to other subjects' content. In this manner, a comprehensive view of the social studies subjects can promote students' interest in and commitment to learning on key global issues and on the social subjects overall, particularly regarding their common core. Thus, subject-integrated teaching can develop students' global citizenship skills and their will to engage in solving key global problems, at present and in the future.